The evolution of Costa Rican contracting: sixty years of scientific publications of the Revista de Ciencias Jurídicas - Díaz Bolaños, Magda (2023)
This document contains an analysis of the evolution of the scientific articles published in the Revista de Ciencias Jurídicas for sixty years in Costa Rica, related to the teaching of contract law.